Searches for B0(s) → J/ψpp[bar] and B + → J/ψ pp[bar] π+ decays - Aaij, Roel; Adeva, B.; Adinolfi, M.; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; et al. (Journal of high energy physics, 2013)
Abstract: The results of searches forB0(s)→J/ψppandB+→J/ψppπ+decays are re-ported. The analysis is based on a data sample, corresponding to an integrated luminosityof 1.0 fb−1ofppcollisions, collected with the LHCb detector. An excess with 2.8σsignifi-cance is seen for the decayB0s→J/ψppand an upper limit on the branching fraction is setat the 90 % confidence level:B(B0s→J/ψpp)<4.8×10−6, which is the first such limit.No significant signals are seen forB0→J/ψppandB+→J/ψppπ+decays, for which thecorresponding limits are set:B(B0→J/ψpp)<5.2×10−7, which significantly improvesthe existing limit; andB(B+→J/ψppπ+)<5.0×10−7, which is the first limit on thisbranching fraction.
Im Titel sind "0" und "+" hochgestellt und "(s)" tiefgestellt
Im Titel steht der zweite Buchstabe p jeweils mit einem Oberstrich
LHCb Collaboration: R. Aaij, B. Adeva, M. Adinolfi, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, O. Grünberg, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, B. Leverington, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 614
Gesehen am 21.04.2021